2016
DOI: 10.1007/s10726-016-9475-9
|View full text |Cite
|
Sign up to set email alerts
|

The MARS Approach in the Verbal and Holistic Evaluation of the Negotiation Template

Abstract: The negotiation template, which defines a set of potential negotiation offers, is traditionally evaluated by means of the simple additive weighting method (SAW). However, some recent research reports on the potential problems and inconsistencies in using and interpreting SAW-based scores. Thus, in this paper we consider the issue of evaluating negotiation offers when the negotiator's preferences are expressed verbally. We present a new approach called Measuring Attractiveness near Reference Situations (MARS), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 39 publications
0
17
0
1
Order By: Relevance
“…It should be noted that, in practice, the decisions made in both stages may be based on a number of criteria. In such cases, various methods for ranking based on multiple criteria (e.g., TOPSIS, see Yoon and Hwang [30], or MARS, see Górecka et al [31]) can be used to rank offers according to the signals observed. The author intends to apply such an approach in the future.…”
Section: Discussion and Future Directions For Researchmentioning
confidence: 99%
“…It should be noted that, in practice, the decisions made in both stages may be based on a number of criteria. In such cases, various methods for ranking based on multiple criteria (e.g., TOPSIS, see Yoon and Hwang [30], or MARS, see Górecka et al [31]) can be used to rank offers according to the signals observed. The author intends to apply such an approach in the future.…”
Section: Discussion and Future Directions For Researchmentioning
confidence: 99%
“…It is based on two methods: revised Simos' procedure [Figueira, Roy, 2002] and ZAPROS [Larichev, Moshkovich, 1995], and aims at obtaining a complete ranking of the alternatives with scores measured on a cardinal scale. The SIPRES method was introduced in 2015 [Górecka, 2015] as a continuation of the works on a tool for the verbal evaluation of the negotiation template connected with the MARS approach [see: Górecka et al, 2014;Górecka et al, 2016]. Based on the original paper, in which two baseline methods were also presented, a detailed description of the SIPRES algorithm is given below.…”
Section: Overview Of the Sipres Methodsmentioning
confidence: 99%
“…This requires a mutual understanding of the counterpart's needs and acknowledging the necessity of making concessions, which inherently makes a problem of developing an adequate negotiation approach. The false assumption regarding such an approach is that it may be either soft or hard (Fisher et al 2011). In fact, neither of these approaches is considered efficient, as they are focused on some social and psychological elements of negotiation game and parties (people) themselves, rather than on the potential value that may be created when the problem under consideration is solved.…”
Section: Introductionmentioning
confidence: 99%